Traditions of Сonfucianism in the higher education system of modern China - Xin, Wang (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The paper examines the meaning-defining role of the Confucian tradition in Chinese culture and education. It substantiates the methodological principles of analysing the Confucian tradition as an essential component of the Chinese system of modern higher education. The paper explicates the main concepts and values of the Confucian philosophy of education. It also explores various interpretations of the role and status of Confucianism in the practical implementation of the strategy for modernising Chinese university education. The paper emphasises the ideological and axiological potential of this educational tradition. The article analyses the social and educational challenges of incorporating Confucian practices into modern Chinese society and discusses some suggestions for preserving and strengthening the influence of Confucianism in the Chinese university education system.